MONITORING OF ACADEMIC AND NON-ACADEMIC FIELDS IN HIGHER EDUCATION - Ali, Ridwan; Maisyaroh, Maisyaroh; Sobri, A. Yusuf (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research aims to present the implementation of academic and non-academic Monitoring in higher education institutions using the literature review method as a source of information. Monitoring in both academic and non-academic fields in higher education is crucial to ensure that the standards of education and educational services provided are met. In the academic field, Monitoring is carried out to ensure that the learning process is effective, the teaching materials are of high quality, and the lecturers have adequate competencies. Meanwhile, in the non-academic field, Monitoring is conducted to ensure that campus security is guaranteed, educational facilities and infrastructure are adequate, and student involvement in campus activities is well-maintained. To improve the effectiveness of Monitoring in both academic and non-academic fields in higher education, universities can implement new strategies and innovations such as utilizing technology, developing evaluation instruments, and increasing student involvement in the Monitoring process. Effective Monitoring will have positive impacts such as improving the quality of education, student satisfaction, lecturer professionalism, campus security, and student involvement in campus activities. Research has shown that effective Monitoring in both academic and non-academic fields in higher education has positive implications for improving the quality of education and educational services. Furthermore, effective Monitoring can positively impact students, lecturers, and the wider community. Therefore, it is important for universities to carry out effective Monitoring in both academic and non-academic fields to ensure that all education and educational services processes meet the established quality standards.